Nominal Suffixes Found in The Game "Final Fantasy VIII" by Square Enix - Pidada, Ida Bagus Oka Wiratama; Ida Bagus Gde Nova Winarta (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The study examines the derivational suffixes, Nominal Suffixes found in the game “Final Fantasy VIII”. It focuses on analyzing the types and morphological processes, providing insights into linguistic structure of the game's language. Descriptive qualitative method was employed, which allowed for an in-depth exploration and elaboration of the data. The analysis was conducted in the framework proposed by Lieber (2009), with additional theoretical support from Plag (2003). The study identified 1,189 words containing derivational suffixes within the game. These suffixes were categorized into four types: nominal, verbal, adjectival, and adverbial. The findings revealed that nominal suffixation occurred in 1.189 instances, accounting for 47.7% of the total. Verbal suffixation was observed in 4 instances, representing a mere 2.0%. Adjectival suffixation was the most prevalent, with 391 instances, making up 42.5% of the identified suffixes. Adverbial suffixation was the least common, with only 2 instances, constituting 7.8 % of the total. The analysis highlights that adjectival suffixation is the most common type of derivational suffixation found in the game. This predominance of adjectival suffixes suggests a linguistic trend within the game's dialogue. This research contributes to a deeper understanding of how derivational processes function in the context of video game linguistics.